ANALISIS KINERJA FINANSIAL BUMN PERIKANAN - MIRA MIRA (Jurnal Ekonomi dan Bisnis, 2010)
The objective of this research is to analyze the financial performance in state own enterprisessof PT Perikanan Nusantara ( PT Usaha Mina, PT Perikanan, PT Tirta Raya Mina, andPT Perikanan Samudra Besar. This Research done on 2009 in each branchs of PT PerikananNusantara. The result show that the cash ratio of PT Perikanan Nusantara is 0.08. TheSolvability value, PT Perikanan Nusantara is below 0.53, though minimum standard of thatsolvability ratio is 1 : 1, in this case cash ratio of PT Perikanan Nusantara is below minimumstandard of solvability ratio. , meaning ability of company to pay for debt of estae had ill assorted.Minimum standard (current ratio 0 which ought to is 2 : 1, in this case current ratio ofPT Fishery of Nusantara reside in far below the mark minimize current ratio that is only 0.24.Meaning, PT Perikanan Nusantara unable to fulfill obligation short-range him, in the formof fluent debt and long-range debt. Depended to this debt can be seen from side of leverageratio PT Perikanan Nusantara which equal to 1.88. This number means that the capital of thecompany is mostly external financing. This suggests that the company depends on the debt,even this company is not stabile yet .Keywords: Cash Ratio, Leverage Ratio, and Solvability Value